2008
DOI: 10.1161/circulationaha.107.712539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Salusin-α and -β on Human Macrophage Foam Cell Formation and Coronary Atherosclerosis

Abstract: Background-Human salusins, related bioactive polypeptides with mitogenic effects on vascular smooth muscle cells and fibroblasts and roles in hemodynamic homeostasis, may be involved in the origin of coronary atherosclerosis. Macrophage foam cell formation, characterized by cholesterol ester accumulation, is modulated by scavenger receptor (cholesterol influx), acyl-coenzyme A:cholesterol acyltransferase-1 (ACAT-1; storage cholesterol ester converted from free cholesterol), and ATP-binding cassette transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
134
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 29 publications
4
134
0
Order By: Relevance
“…So we speculated that serum salusin-alpha levels might be associated with both initial and advanced atherosclerosis. Shichiri et al 8 have shown that salusin-alpha suppresses foam cell formation in human monocyte-derived macrophages in acute coronary syndrome, contributing to its anti-atherosclerotic effect. Therefore, it is possible that decreased salusin-alpha may have a causal role in the process of atherosclerotic plaque formation.…”
Section: Salusin-alpha Is Associated With Preclinical Atheroscleroticmentioning
confidence: 99%
See 1 more Smart Citation
“…So we speculated that serum salusin-alpha levels might be associated with both initial and advanced atherosclerosis. Shichiri et al 8 have shown that salusin-alpha suppresses foam cell formation in human monocyte-derived macrophages in acute coronary syndrome, contributing to its anti-atherosclerotic effect. Therefore, it is possible that decreased salusin-alpha may have a causal role in the process of atherosclerotic plaque formation.…”
Section: Salusin-alpha Is Associated With Preclinical Atheroscleroticmentioning
confidence: 99%
“…It was reported that development of atherosclerosis may be accelerated by salusin-beta and suppressed by salusin-alpha via acyl-CoA cholesterol acyltransferase-1(ACAT-1) regulation in acute coronary syndrome. 8 Previous study 9 has shown that serum salusin-alpha levels are decreased and correlated negatively with maximum IMT in essential hypertensive patients.…”
Section: Introductionmentioning
confidence: 97%
“…Both the formation of macrophage foam cells and the development of atherosclerosis are suppressed by salusin-α (7). Serum salusin-α levels are also reported to be significantly lower in patients with coronary artery disease, and in hypertensive patients in whom the salusin-α level is inversely associated with carotid atherosclerosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Salusins mainly affect the cardiovascular system (5)(6)(7)(8). Salusin-β is the most hypotensive peptide: its infusion rapidly and profoundly decreases blood pressure (BP) and heart rate (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation